Building A Religious Tourism Village: An Ethnographic Study of the Emergence of Intellectual Authority - Indra Pratama Putra Salmon (Perkumpulan Ahli Manajemen Dakwah Indonesia (PAMDI), 2025)
Purpose – The Indonesian government is promoting religious moderation as a counter-narrative to extremism and intolerance. The propagation of this ideology is facilitated by a variety of strategies, including the establishment of religious tolerance tourism villages. This article aims to elucidate the process of establishing a religious tourism village in Rama Agung Village, North Bengkulu Regency, Indonesia. Design/methodology/approach – This research has been in progress since 2022, with data collection and analysis ongoing until 2024. During this period, we engaged in repeated fieldwork, which included conducting in-depth interviews and observations, as well as participating in a series of village activities. The ethnographic procedure was meticulously divided into four stages: preliminary fieldwork, fieldwork, data processing and analysis, and the presentation of findings. The collected data was then subjected to a rigorous analysis using a systematic coding, categorization, and placement system. Findings – Despite initial rejection during its nascent stages, academics ultimately emerged as a pivotal element in the successful establishment of the five-religion tourist village in Rama Agung. This recognition was achieved after the village underwent various stages of development. The following stages were identified: 1) government support; 2) ideas and assistance from academics; 3) cross-sectoral coordination and the formation; 4) internal village coordination and the formation of the Interfaith Community Forum (FPUB); 5) tourist attractions; and 6) participation in competitions. Research implications – This article presents significant findings for practitioners in the field of religious tourism, underscoring the necessity for academics to be entrusted with the authority to develop innovations tailored to the potential of villages. This authority will ultimately result in the establishment of FPUB as a counterbalance in decision-making, thereby reducing conflicts and jealousy in villages. Originality/value – Research on religious tourism villages and tolerance villages remains sparse due to the nascent state of this model. Consequently, there is a necessity for efforts to document a variety of perspectives to increase knowledge. This is the inaugural study to delineate the process of establishing a tourism village based on five different religions. Keywords - Religious tourism, Tourism village, Stakeholders, Desa Rama Agung. Paper type - Research paper